Effectiveness of pictorial based self-management among adult with asthma in a suburban primary care health clinic: A randomised controlled trial - Mohd Radzniwan A Rashid; Chow S.Y.; Shamsul A.S.; Ali M.F. (Ministry of Health, 2024)
Indexed by Scopus